Fe-fe2(so4)3-fe(oh)3-fe2o3-fe-fes-h2s-so2-so3-h2so4-na2so4-baso4

2005лизок 2005лизок    3   26.09.2019 05:40    0

Ответы
zaharkakorsunov zaharkakorsunov  08.10.2020 20:03
2Fe + 3H2SO4 = Fe2(SO4)3 + 3H2

Fe2(SO4)3 + 6NaOH = 2Fe(OH)3 + 3Na2SO4

2Fe(OH)3 (t)= Fe2O3 + 3H2O

2Fe2O3 (t)= 4Fe + 3O2

Fe + S = FeS

FeS + 2HCl = FeCl2 + H2S

2H2S + 3O2 = 2SO2 + 2H2O

2SO2 + O2 = 2SO3

SO3 + H2O = H2SO4

H2SO4 + 2Na = Na2SO4 + H2

Na2SO4 + Ba(OH)2 = 2NaOH + BaSO4.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Химия